Release of protein N-glycans by effectors of a Hofmann carboxamide rearrangement - Kasim, Mumtaz; Schulz, Malissa; Griebel, Anja; Malhotra, Akshay; Müller, Barbara; von Horsten, Hans Henning (Frontiers in Molecular Biosciences, 2022)
Background Chemical methods for glycan release have gained traction because of their cost efficiency, ac-celerated reaction time and ability to release glycans not amenable to enzymatic cleavage. Oxi-dative chemical glycan release via hypochlorite treatment has been shown to be a convenient and efficient method that yields N-glycans similar to classical PNGase F digestion. We ob-served that the initial steps of the suggested mechanism for the oxidative release of glycans from glycoproteins by hypohalites showed similarities to the initiating steps of the classical Hofmann rearrangement of carboxamides. Therefore, we investigated the ability of different stable effectors of a Hofmann-type carboxamide rearrangement to efficiently and selectively release N-glycans from glycoproteins. Methods Released glycans obtained from different experimental chemical release approaches were ana-lyzed by HILIC-FLD, BHZ-FACE and ESI-MS and evaluated with respect to electrophoretic mobility, retention time and integrated peak area for resolved glycans. Results We show that the known Hoffmann catalysts 1,3-dichloro-5,5-dimethylhydantoin, the hyperva-lent organoiodine (III) compound diacetoxy-iodobenzene as well as in-situ hypobromite genera-tion using Oxone® and potassium bromide are all capable of releasing protein-bound N-glycans in good yield. Among the compounds investigated, diacetoxy-iodobenzene was capable of re-leasing glycans in the absence of alkali. Detailed investigations of the bromide/Oxone® method revealed a dependence of N-glycan release efficiency from the temporal order of bromide addi-tion to the reaction mix as well as from a molar excess of bromide over Oxone®. Conclusions These findings suggest that the oxidative release of N-glycans occurs via the initiating steps of a Hofmann carboxamide rearrangement. Hypervalent organoiodine compounds hold the promise of releasing glycans in the absence of alkali. The in-situ generation of hypobromite by bro-mide/Oxone® produces a consistent defined amount of reagent for rapid N-glycan release for both analytical and preparative purposes